KEBIJAKAN KRIMINALISASI TERHADAP PERBUATAN KUMPUL KEBO - Dwi Wiranata, I Gst Ngr; R., Ibrahim (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 03, Juli 2013, 2013)
The action of cohabitation to be one of criminal to criminalize the thing wich has recently based the concept of penal law, because cohabitation is regarded as the action wich does not agree with the tradition and religius norm applying in Indonesia. Moreever, cohabitation could categorized as social desease. It so happens, the problem wich is being discussed in this short paper seeking the problem on the importance of criminalization toward the cohabitation viewed from the penal law policy and also the use of penal law implementation in anticipacing and resolving the case of cohabitation in Indonesia. It show that the criminalization of cohabitation should be conducted accordingly as the action of cohabitation, because is not compliant agree with the tradition and religius norm applying in Indonesia. Beside, criminalization should stand on the substance/element of value, justice and the law supremacy so that it can be implemented in the form of to reflect the identity of Indonesia. The methodolody used in this research is normative yuridical one wich means to focus on the researc of library research.
Keywords: criminalization policy, cohabitation